Analysis of the Relationship Between Workload, Work Stress, and Work Motivation of Healthcare Providers and Medical Staff on Patient Loyalty - Muhammad Dezha Detiro; Sonya Dewi Wulandari; Dicky Yulius Pangkey (CV. Global Health Science Group, 2025)
High-quality healthcare services in outpatient units largely depend on the effectiveness of human resources, particularly in relation to workload, work stress, and work motivation among healthcare workers. This study aims to analyze the relationship between workload, work stress, and work motivation on patient loyalty at the Outpatient Unit of the Dental and Oral Hospital (RSGM) UNJANI. This research employed an analytical quantitative method with a cross-sectional approach. The sample consisted of 69 healthcare workers and 100 outpatients. Data collection instruments included the NASA-TLX questionnaire to assess workload, the PSS-10 to measure work stress, an adapted Minnesota Work Motivation Questionnaire to evaluate work motivation, and SERVQUAL to assess patient loyalty. Validity testing showed p-values < 0.05, indicating that all instruments were valid, while reliability testing revealed Cronbach’s Alpha values > 0.7, confirming the instruments’ reliability. Data analysis was performed using Spearman correlation and multiple linear regression tests. The results showed a significant relationship between workload and work stress with patient loyalty (ρ = -0.569 and -0.513; p < 0.01), as well as a positive relationship between work motivation and patient loyalty (ρ = 0.556; p < 0.01). Multivariate analysis indicated that work motivation was the most dominant factor influencing patient loyalty compared to workload and work stress. These findings highlight the importance of effective human resource management in improving service quality and maintaining patient loyalty in outpatient settings.